Pulse Effect of Precipitation: Spatial Patterns and Mechanisms of Soil Carbon Emissions - Jiang, Zhaoxia; Bian, Hongfeng; Xu, Li; Li, Mingxu; He, Nianpeng (Frontiers in Ecology and Evolution, 2021)
The rapid and strong release of CO2 caused by precipitation (known as the pulse effect) is a common phenomenon that significantly affects ecosystem C cycling. However, the degree at which the pulse effect of precipitation occurs at large regional scales remains unclear. In this study, we conducted continuous and high-frequency measurements of soil CO2 release rates (Rs) for 48 h after simulated precipitation, along a transected precipitation gradient of different grassland types (i.e., covering meadow, typical, and desert) in Inner Mongolia, China. Pulse effects were assessed using the maximum Rs (Rsoil-max) and accumulated CO2 emissions (ARs-soil) data. Strong precipitation pulse effects were found in all sites; however, the effects differed among grassland types. In addition, an apparent decrease in both Rsoil-max and ARs-soil was observed from the east to west, i.e., along the decreasing precipitation gradient. Furthermore, Rsoil-max and ARs-soil were significantly positively correlated with soil quality (SOC, POC, N, etc.). ARs-soil was also significantly positively correlated with soil microbial biomass. Rsoil-max and ARs-soil were found to have similar spatial variations and controlling mechanisms. These results greatly support the substrate supply hypothesis for the effects of precipitation pulses, thus, demonstrating a good perspective for their prediction. Our findings also verified the significant effect of soil CO2 release from precipitation pulses on the grasslands of arid and semi-arid regions. Our data provide a scientific basis for model simulations to better predict the responses of ecosystem carbon cycles in arid and semi-arid regions under predicted climate change scenarios.